Developing dimensions and indicators to measure decentralization in decentralized autonomous organizations - Hyejin Park; Ivan Ureta; Bo-Young Kim (Administrative Sciences, 2023)
Decentralization holds a significant role in the context of decentralized autonomous organizations (DAOs), with its nature being not a fixed value but a comparative spectrum. Prior research investigating the measurement of decentralization in nations' governance system provides a foundation for our current study. This research aims to integrate these insights to define dimensions and indicators, tailored explicitly for assessing decentralization levels within DAOs. Then, the article undertakes an examination of the suitability of traditional decentralization measurement approaches within the unique DAO context, employing confirmatory factor analysis (CFA) as our analytical tool based on a total of 44 DAOs. Hence, the results suggest that DAOs have three dimensions for measuring decentralization, 'political decentralization as a participatory engagement', 'economic decentralization as a resource distribution', and 'administrative decentralization as the self-governing execution of decisions'. By substantiating the applicability of established decentralization measurement frameworks within the unique context of DAOs, the findings not only enhance the understanding of this emergent governance paradigm but also provide DAO practitioners, policymakers, and researchers with invaluable insights.
Keywords: 350; confirmatory factor analysis; decentralization; decentralized autonomous organization; decentralized technologies; innovative organization